Effect of different levels of lysine and fiber degrading enzyme on growth rate and GUT development in the starter phase of slow-growing Ayam SAGA - Mohd Nadzir, Mohd Noor Hisham; N. A, Nor Izwan Hakimi; A. R, Roziatul Erin; R., Sarah; I., Norham; R., Muhammad Rusydi; M., Harivanthan; Samat, Noraini (Malaysian Society of Animal Production (MSAP), 2024)
This study investigated the impact of varying levels of the essential amino acid lysine and the fiber-degrading enzyme B-mannanase on growth performance and gut morphology in the starter phase of slow-growing Ayam SAGA. The study aimed to optimize the utilization of Palm Kernel Cake (PKC), which is rich in fiber, as a sustainable feed ingredient for monogastric animals. Utilizing a 3x3 factorial design with a Randomized Complete Block Design (RCBD), the experiment involved nine treatment groups with three replicates each. The results revealed that the highest level of lysine (120% NRC) combined with 0.4% B-mannanase (T9) significantly enhanced gizzard weight, jejunal and ileal development (p < 0.05), which correlated with improved Body Weight Gain (BWG) and a reduced Feed Conversion Ratio (FCR) in Ayam SAGA. However, Feed Intake (FI) was not significantly affected by the enzyme-lysine combination. These findings suggest that the optimized combination (120% NRC lysine, 0.4% B-mannanase) can improve nutrient absorption and growth efficiency, potentially enhancing the sustainability of poultry production using PKC-based diets.